Anesthetic Management of a Patient With Tracheal Dehiscence Post–Tracheal Resection Surgery. (December 2017) - Kim, Sang; Khromava, Maryna; Zerillo, Jeron; Silvay, George; Levine, Adam I.
We present a case of a patient with complete tracheal dehiscence and multiple false passages after recent tracheal resection and anastomosis. Loss of tracheal continuity after disruption of anastomosis with distal stump retraction presents a unique anesthetic challenge given lack of access to the trachea and the need for adequate anesthesia and analgesia for surgical neck dissection. Traditional airway management, including awake fiberoptic intubation, intubation via direct laryngoscopy, needle cricothyrotomy, and awake tracheostomy are not viable options. Using total intravenous anesthesia with spontaneous ventilation, surgeons dissected the neck, retrieved the distal tracheal stump, repaired the trachea, and formalized the tracheostomy. We highlight the importance of recognizing the symptoms of a tracheal rupture, understanding the extreme limitation of securing the airway with traditional techniques, and discuss the alternative techniques including use of extracorporeal membrane oxygenation to avoid airway management. Awareness of increased mortality risk with tracheal reoperation and the significance of close communication between the anesthesiologists, the surgeons, and the patient is necessary for successful management.